Associating blind user-designer product experience through design activities / Verly Veto Vermol - Vermol, Verly Veto (Institute of Graduate Studies, UiTM, 2018)
The lack of blind user experience understanding in design knowledge may lead to confusing preferences that are associating them with the designer in product development. Blind user touch experience feedback remarks important attributes to supply designer knowledge in designing through blind user familiarity. The problem of associating this knowledge cannot be solved simply by asking questions and surveys. There is an urgent need for an innovative approach to design activities, through product design investigation. Thus, the adoption of a strategic procedural design activity approach is needed to carry further identifying haptic imaging function and roles. This research trigger to associate attributes that influencing the blind user and designer through their experience. It specifically studies product components representation to design preferences and attributes. This research is based on data obtained from protocol interviews and observation that polled blind users and designers haptic feedback to product attributes factors from experiencing the complexity of haptic imaging modalities. The data were analysed to evaluate and determine the product attributes and its level of preferences that are influencing the strategic approach to the design development planning and management of product appearance for the blind user. The research suggested that successful procedural design activities are able to associate designers' understanding of product physical and functional qualities feedback draws from the understanding of the blind user. The results of the study provide designer product sketch idea feedback pattern through haptic experience which incorporate principal issues discussed that associated to the product performances.